Recent Advances of STATCOM in Power Transmission Lines – A Review - et.al, Mr. L NarayanaGadupudi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Internal Liability of power system transmission lines influenced by the turbulences owing to catastrophic disasters. In order to achieve Constant Voltage Stability at both ends of the transmission lines, Static Synchronous Compensator (STATCOM) is imperative. Voltage source Converter mechanisms augment with switching frequency control methodologies are widely adopted to regulate the reactive power. By deliberating IEEE Standards, the minimization of Total Harmonic Distortion (THD) is conceivable with STATCOM. This paper depicts the advancement of VSC based STATCOM approaches and the methodologies to minimize the switching losses. Economical management of High-Power ratings systems is also discussed in this paper